Crossover to the KPZ equation - Gonçalves, Patrícia (2010)
We consider the weakly asymmetric simple exclusion process and we show that the density field is governed by an Ornstein-Uhlenbeck process for strength asymmetry n2-γ if γϵ (1=2; 1), while for γ= 1=2 it is an energy solution of the KPZ equation.